Modelling metal complexation in solvent extraction systems - Lunkov, Sergey (Curtin University, 2013)
This thesis represents a theoretical investigation of synergistic solvent extraction of transition metal ions based on models for the commercial used components, namely LIX63 and Versatic10 acid. Quantum mechanical studies of oxime isomerisation have been conducted in order to understand the thermodynamic and kinetic properties of the syn/anti interconversion of LIX63, which is found to favour an oligomeric form in non-polar solvents.